Pengaruh Kepemimpinan Transformasional, Kompetensi, Kompensasi dan Komitmen terhadap Budaya Organisasi serta Implikasinya pada Kinerja Dosen - Yohny Anwar (Kontigensi : Jurnal Ilmiah Manajemen, 2016)
This study aims to analyze the influence of Transformational Leadership, Competence, Commitment, Compensation toward Organizational Culture and its Implications on Lecturer performance. This research is compiled in the form of Proportional Cluster Random Sampling and sample size was set at 257 respondents. Data were analyzed using path analysis. The results of data analysis showed that the descriptive analysis, Transformational Leadership fairly good, Competence fairly good, Compensation fairly good, Commitment fairly good, Organizational Culture fairly good, Lecturer Performance fairly good. The results of the verification analysis showed a significant effect of transformational leadership on organizational culture, a significant difference between the competences of the organization's culture, a significant difference between the compensation of the Cultural Organization, a significant difference between the competences of the Organizational Culture. There is a simultaneous effect between transformational leadership, competence, Compensation, and Organizational Commitment to Culture. There is the influence of organizational culture on the Performance of Private Lecturer at the University of North Sumatra.